WORKERS IN NUTMEG PLANTATIONS AND THE TOWN OF NEIRA IN THE BANDA ISLANDS DURING THE 17-19TH CENTURY (A DISCIPLINARY PANOPTICON MODEL) - Sarjiyanto, Sarjiyanto; Marwoto, Irmawati (International Review of Humanities Studies, 2019)
Nutmeg plantations in the Banda Islands, Central Maluku, had an important value in the early history of industrial development in Indonesia. The operational management of planting, maintaining, picking, processing, distribution and exercising power are some lessons learned. Plantations at that time also required various forms of human resource management, ranging from recruitment, division of labor, supervision and discipline of its workers. In this case the material culture reflects the mindset of the builders and managers of the time. Through descriptive qualitative methods, disciplinary problems related to the management of the nutmeg plantations are discussed by linking the concepts of technofact, sociofacts, ideofacts in archeology with the concept of panopticon as a disciplinary model proposed by Foucault. The goal is to explore the values that can be applied to the present from the remnants associated with the nutmeg plantations of the Banda Islands. The results obtained are related to the discipline model with archeological remains related to the management of nutmeg plantations. The concept of panopticon is still relevant today, with necessary modifications in the form of cultural products, and adjustments in the development of technology and information.